Mediating Role of School Variables in Anticipating Blocks and Consequences Creativity among Rural Adolescents - Sheoran, Sumit; Dhanda, Bimla; Malik, Joginder Singh (Indian Journal of Extension Education, 2021)
Each developmental stage upholds new and its own unique competency requirements, challenges, struggles and opportunities for personal human growth. When an individual is in their early adolescence phase, his/her creativity is greatly influenced by its surroundings and school environment is one of those crucial factors. Hence, the present study was planned to explore the mediating role of school environment in students’ blocks and consequences creativity. The primary data was collected from 300 academically bright rural young adolescents. Z-test and ANOVA were administered to discover the influence of independent variables (school environment) on the dependent variables (blocks and consequences creativity). Results elucidated significant differences in blocks fluency, consequences originality and consequences creativity across school type, academic class and teaching method employed by the teachers. Blocks flexibility had significant differences across school type and academic class. Blocks originality was observed to have significant differences across academic class and consecutive academic record. It was revealed that blocks creativity had significant differences across all the independent variables. Consequences fluency of the students had significant differences across school type, academic class and consecutive academic record.